2010
DOI: 10.1107/s1600536810022506
|View full text |Cite
|
Sign up to set email alerts
|

N-[(2S)-2-(4-Bromophenyl)-4-oxo-1,3-thiazolidin-3-yl]pyridine-3-carboxamide

Abstract: In the title compound, C15H12BrN3O2S, the dihedral angle between the pyridine and benzene rings is 73.17 (19)°. The five-membered 1,3-thia­zolidine ring has an envelope conformation, with the S atom displaced by 0.196 (1) Å from the mean plane of the four other ring atoms. An intra­molecular C—H⋯N inter­action occurs. The crystal structure is stabil­ized by inter­molecular N—H⋯O and C—H⋯O hydrogen bonds and C—H⋯π inter­actions. In addition, a weak π–π stacking inter­action is also observed between the 1,3-thia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…The packing in the title crystal structure can be described as asuccessionofparallel layers.The conjugationbetween C=Oand the amiden itrogeni se vident from thev alue of theb ondl ength d(Nl-C10) =1.362(5)Å.The thiazole ring is planar as indicated by torsion angles ÐC9-C10-N1-C14 =-3.4(5)°, ÐN1-C10-C9-S2 =0.4(4)°, ÐC10-C9-S2-C14 =1.8(3)°and ÐN1-C14-S2-C9 =-36(3)°. In addition, the torsion angles ÐS2-C14-N2-C15 =0 .8(6)°, ÐO1-C10-N1-C11 =1 .2(6)°, ÐN2-C14-N1-C11 =1.8(6)°, ÐC5-C8-C9-S2 =-1.0(7)°and ÐN1-C10-C9-S2 =0 .4(4)°revealed that the thiazole ring is coplanar with O1, N2,C 5, C8,C 11 and C15.T he distances.362(5) Åagree with the literature reports [21][22][23][24][25]. The bond length d(C14-N2) =1.259(5) Åand the angles ÐN2-C14-S2 =128.2(3)°and ÐN2-C14-N1 =121.8(4)°con-firm the imine nature of the N2-C14 bond.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…The packing in the title crystal structure can be described as asuccessionofparallel layers.The conjugationbetween C=Oand the amiden itrogeni se vident from thev alue of theb ondl ength d(Nl-C10) =1.362(5)Å.The thiazole ring is planar as indicated by torsion angles ÐC9-C10-N1-C14 =-3.4(5)°, ÐN1-C10-C9-S2 =0.4(4)°, ÐC10-C9-S2-C14 =1.8(3)°and ÐN1-C14-S2-C9 =-36(3)°. In addition, the torsion angles ÐS2-C14-N2-C15 =0 .8(6)°, ÐO1-C10-N1-C11 =1 .2(6)°, ÐN2-C14-N1-C11 =1.8(6)°, ÐC5-C8-C9-S2 =-1.0(7)°and ÐN1-C10-C9-S2 =0 .4(4)°revealed that the thiazole ring is coplanar with O1, N2,C 5, C8,C 11 and C15.T he distances.362(5) Åagree with the literature reports [21][22][23][24][25]. The bond length d(C14-N2) =1.259(5) Åand the angles ÐN2-C14-S2 =128.2(3)°and ÐN2-C14-N1 =121.8(4)°con-firm the imine nature of the N2-C14 bond.…”
mentioning
confidence: 82%
“….362(5) Åagree with the literature reports [21][22][23][24][25]. The bond length d(C14-N2) =1.259(5) Åand the angles ÐN2-C14-S2 =128.2(3)°and ÐN2-C14-N1 =121.8(4)°con-firm the imine nature of the N2-C14 bond.…”
Section: Discussionmentioning
confidence: 99%